Equality of opportunities for next generation researchers in Europe: a snapshot discussion motivated by the ERC statistics - N. Žagar; N. Žagar; T. Schäfer; T. Schäfer (Advances in Geosciences, 2020)
This paper reflects on the results of a survey carried out within the COST TN1301 Sci-Generation network among the holders of ERC starting grants originating from countries of Central and Eastern Europe. The results of the survey reveal a greater personal satisfaction of the grant holders when carrying out the ERC-funded research in their native countries following successful PhD and/or post-doctoral periods in Western Europe and the USA. On the downside, a tenacious administration appears to be the largest burden for a new generation of successful researchers. It is discussed how the the statistics of ERC starting grants is a mirror of host countries' and host institutions' ability to attract and keep the most talented young researchers.